Electron irradiation induced transformation of (Pb5Ca5)(VO4)6F2 apatite to CaVO3 perovskite - Sun, K. (2013)
Crystallochemical changes of (Pb5Ca5)(VO4)6F2 apatite under electron irradiation were examined by transmission electron microscopy. The apatite, a synthetic analog of vanadinite, was moderately stable towards a less intense 300-keV LaB6 source, while it changed rapidly in structure when exposed to the higher flux of a 200-keV field emission gun. The electron beam induced transformation of vanadinite proceeds sequentially by (i) migration and loss of fluorine, (ii) lead volatilization and conversion to 2–5-nm platelets of a glaserite-type structure, and (iii) the reduction of V5+ to V4+ with the removal of lead and calcium oxide that leads to single-crystal CaVO3 perovskite as the ultimate product. The phase transformations are interpreted based on the crystallographic relations among the CaVO3 perovskite, the (Pb5Ca5)(VO4)6F2 apatite and the glaserite-type structures, and compositional changes under electron irradiation.